2009
DOI: 10.1098/rsbl.2008.0764
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural phase polyphenism in the Australian plague locust ( Chortoicetes terminifera )

Abstract: Swarming and the expression of phase polyphenism are defining characteristics of locust species. Increases in local population density mediate morphological, physiological and behavioural changes within individuals, which correlate with mass marching of juveniles in migratory bands and flying swarms of adults. The Australian plague locust ( Chortoicetes terminifera ) regularly forms migratory bands and swarms, but is claimed not to express phase polyphenism and has accordingly been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…Our study suggested that the migratory locust displays a different time course of behavioral phase change as compared with the desert locust, Schistocerca gregaria [44], and the Australian plague locust, Chortoicetes terminifera [45]. We identified several candidate gene categories involved in the fundamental phase-defining behavioral differences in locusts, and characterized the functions of CSP and takeout genes, which mediate the rapid switch of attraction/repulsion behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…Our study suggested that the migratory locust displays a different time course of behavioral phase change as compared with the desert locust, Schistocerca gregaria [44], and the Australian plague locust, Chortoicetes terminifera [45]. We identified several candidate gene categories involved in the fundamental phase-defining behavioral differences in locusts, and characterized the functions of CSP and takeout genes, which mediate the rapid switch of attraction/repulsion behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…Chortoicetes terminifera is an endemic species that can experience huge increases in local population density, with individuals actively aggregating and forming migratory bands and swarms that can damage pastures and crops [22]. Given its broad geographical range and potential to mass migrate, an improved understanding of its movement patterns and population dynamics is of critical importance to its management.…”
Section: Introductionmentioning
confidence: 99%
“…() demonstrated that longer assessment using this assay did not improve the method. To hasten the process of analysis and the time needed to assess a group of individuals, automated computer analyses were developed (Gray et al., ; Cullen et al., ). The rapid time course of behavioural gregarization has been reported (Rogers et al., ).…”
Section: Discussionmentioning
confidence: 99%